When Wanting the Best Goes Right or Wrong: Distinguishing Between Adaptive and Maladaptive Maximization. (April 2017) - Hughes, Jeffrey; Scholer, Abigail A.
Researchers have often disagreed on how to define maximization, leading to conflicting conclusions about its potential benefits or drawbacks. Drawing from motivation research, we distinguish between the goals (i.e., wanting the best) and strategies (e.g., alternative search) associated with maximizing. Three studies illustrate how this differentiation offers insight into when maximizers do or do not experience affective costs when making decisions. In Study 1, we show that two motivational orientations, promotion focus and assessment mode, are both associated with the goal of wanting the best, yet assessment (not promotion) is related to the use of alternative search strategies. In Study 2, we demonstrate that alternative search strategies are associated with frustration on a discrete decision task. In Study 3, we provide evidence that one reason for this link may be due to reconsideration of previously dismissed options. We discuss the potential of this approach to integrate research in this area.